PENGARUH KALSIUM TERHADAP TUMBUH KEMBANG GIGI GELIGI ANAK - Amandia Dewi Permana Shita; Sulistyani Sulistyani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Adequate amounts of Calcium ions are essential for the developmental of enamel, dentin, and cementum. The delivery of adequate amounts of calcium to the dental tissues during developmental is essentially dependent on the maintenance of normal calcium concentrations in the extracellular fluids. Since the homeostatic mechanisms controlling the extracellular calcium ions concentration are highly efficient, only the most severe forms of calcium deprivation can result inhypocalcification of the dental tissues. Genetic defects or deficiencies of nutrients in addition to calcium may result in the formation of abnormal enamel, dentin or cementum.